2001
DOI: 10.1016/s0006-3495(01)76137-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Structure of Dimyristoylphosphatidylcholine Bilayers with Cholesterol, Ergosterol, and Lanosterol

Abstract: Five molecular dynamics computer simulations were performed on different phospholipid:sterol membrane systems in order to study the influence of sterol structure on membrane properties. Three of these simulated bilayer systems were composed of a 1:8 sterol:phospholipid ratio, each of which employed one of the sterol molecules: cholesterol, ergosterol, and lanosterol. The two other simulations were of a bilayer with a 1:1 sterol:phospholipid ratio. These simulations employed cholesterol and lanosterol, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
120
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 35 publications
23
120
3
Order By: Relevance
“…Kucerka et al 16 used molecular simulations to relate the simulated bilayer structure to experimental X-ray results thereby allowing a detailed comparison to the experimental models. Earlier studies 13,[19][20][21][22][23][24][25] used a united-atom model to investigate the impact of cholesterol and other sterol molecules on lipid bilayers. These studies use effectively less atoms by grouping a few of the atoms together.…”
Section: Introductionmentioning
confidence: 99%
“…Kucerka et al 16 used molecular simulations to relate the simulated bilayer structure to experimental X-ray results thereby allowing a detailed comparison to the experimental models. Earlier studies 13,[19][20][21][22][23][24][25] used a united-atom model to investigate the impact of cholesterol and other sterol molecules on lipid bilayers. These studies use effectively less atoms by grouping a few of the atoms together.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] By using FTIR spectroscopy to study anhydrous lipid mixtures, Wong et al have demonstrated that hydrogen bonding occurs between the cholesterols OH group and the lipids sn-2 chain carbonyl and phosphate groups. [9] However, no evidence of hydrogen bonding between cholesterol and the carbonyl groups at the diester [ Abstract: The complete assignment of cholesterol 1 H and 13 C NMR resonances in a lipid bilayer environment (l adimyristoylphosphatidylcholine/cholesterol 2:1) has been obtained by a combination of 1D and 2D MAS NMR experiments: these variations were attributed to local changes around the cholesterol hydroxy group, such as the three major rotameric states of the C3ÀO3 bond and different hydrogen bonding partners (water molecules, carboxy and phosphodiester groups of phosphatidylcholine). Comparison of the experimental and theoretical chemical shifts obtained from quantum-chemistry calculations of various transient molecular complexes has allowed the distributions of hydrogen bonding partners and hydroxy rotameric states to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…[26] The results of earlier studies indicated that a hydrogen bond exists between the hydroxy group of cholesterol and the phosphate headgroup of a phospholipid. [27] However, the presence of such a hydrogen bond was refuted by subsequent 13 C and 31 P NMR spectroscopic studies. [28] Therefore, the molecular basis of the cholesterol-phosphatidylcholine association has not been unequivocally established.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the experiments are performed at a temperature below the T M , our liposomes can therefore be considered in the gel phase state [Tristram-Nagle and Nagle, 2004]. Moreover, it is well known that the presence of CHO increases the passive permeability of bilayers below the T M [Smondyrev and Berkowitz, 2001], but in our CAloaded liposomes the substrate showed a very low selfdiffusion rate, and, further, we always compared the data between sham and exposed samples, to avoid the contribution of any possible effects other than those induced by the radiation itself. These enzyme-containing liposomes can, therefore, be considered to be retaining typical permeation rates of solute across lipid bilayers [Cevc, 1993], and enabling a direct comparison with the permeability function of lipid bilayers in cell membranes.…”
Section: Discussionmentioning
confidence: 99%